2012
DOI: 10.2519/jospt.2012.4243
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Clinical Prediction Rule to Identify Patients With Neck Pain Likely to Benefit From Thrust Joint Manipulation to the Cervical Spine

Abstract: Study Design Prospective cohort/predictive validity study. Objective To determine the predictive validity of selected clinical examination items and to develop a clinical prediction rule to determine which patients with neck pain may benefit from cervical thrust joint manipulation (TJM) and exercise. Background TJM to the cervical spine has been shown to be effective in patients presenting with a primary report of neck pain. It would be useful for clinicians to have a decision-making tool, such as a clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 74 publications
5
45
2
1
Order By: Relevance
“…The outcomes of this study are consistent with the findings of the study by Puentedura et al 12 that positive expectations are of prognostic value for predicting favorable outcomes. The authors note that patients will prefer particular treatments because of an expectation of benefit from that treatment.…”
supporting
confidence: 82%
“…The outcomes of this study are consistent with the findings of the study by Puentedura et al 12 that positive expectations are of prognostic value for predicting favorable outcomes. The authors note that patients will prefer particular treatments because of an expectation of benefit from that treatment.…”
supporting
confidence: 82%
“…Finally, we assessed potential adverse effects of the spine thrust manipulation at short-term follow-up (1 week). 37 Few patients (3%) reported adverse effects after the cervical spine thrust manipulation, which is a lower percentage than that of a previous study 44 but similar to others. 37,38 This may be related to the restrictive inclusion criteria of the current study or the fact that we only included a short-term follow-up period for adverse effects, as it has been suggested that adverse events can occur up to 1 month after treatment.…”
Section: Discussioncontrasting
confidence: 44%
“…As a useful base for making decisions whether to apply or for which individuals to consider thrust manipulation, an attempt has been performed to identify those who would potentially benefit from manipulation. Among the four clinical criteria, duration of symptoms less than 38 days, expectation of the helpfulness of manipulation, a 10° or more difference of cervical rotation range of motion between sides, and provocation of pain with posteroanterior spring test, the presence of three or four criteria was found to improve the probability of success of thrust manipulation from 39% to 90% in patients with neck pain complaints without the exclusion of discogenic neck pain, but with the exclusion of them with two or more positive nerve root compression signs (60). Regarding safety of cervical manipulation, which is also a very important issue, a systematic review reported no serious adverse events resulting from the use of cervical manipulation except for minor ones, including transient neurological deficits and an increase in neck pain.…”
Section: Manipulation and Mobilizationmentioning
confidence: 99%